1999
DOI: 10.1238/physica.regular.060a00589
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Spectroscopy of Porous Silicon

Abstract: Large photoinduced transmission and reflection is observed in porous silicon (PS) films in the spectral region 1.6–3.2 eV by using a femtosecond pump-supercontinuum. probe technique. The measured nonlinear transmission and reflectivity spectra have a fast component ~500 fs. The spectral structure and relaxation dynamics of the short-lived component with slowing down of relaxation rate at ~1.95 eV and ~2.5 eV are suggestive that relaxation processes correspond to nanocrystallites defects scattering. Observed co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…22 Silicon grains showed a fast decay component of 400 fs, attributed to the quenching of the interior exciton radiative recombination by carrier trapping, 23 while another study found a 500 fs component attributed to nanocrystallite defect scattering. 24 Other investigations observed a femtosecond component that was proposed to be due to molecule-like silicon complexes or clusters in the material. 25,26 Additionally, a feature that decayed in ∼3 ps was monitored and found to be dependent on the porosity of the sample.…”
mentioning
confidence: 99%
“…22 Silicon grains showed a fast decay component of 400 fs, attributed to the quenching of the interior exciton radiative recombination by carrier trapping, 23 while another study found a 500 fs component attributed to nanocrystallite defect scattering. 24 Other investigations observed a femtosecond component that was proposed to be due to molecule-like silicon complexes or clusters in the material. 25,26 Additionally, a feature that decayed in ∼3 ps was monitored and found to be dependent on the porosity of the sample.…”
mentioning
confidence: 99%
“…The time evolution of the PIA and PIB, shown in Figure , has been extracted from the biexponential curve fitting model given by eq : normalΔ A = normalΔ A 0 + A 1 * exp ( prefix− t τ 1 ) + A 2 * exp ( prefix− t τ 2 ) where τ 1 and τ 2 are defined as states decay lifetimes with their respective amplitude weights A 1 and A 2 given as a percentage with the lifetime in Table S1. Figure shows the decay dynamics of various states for transient absorption at the 400 nm excitation wavelength . The transient absorption dynamics results have been divided into two distinct regions: the cavity mode (λ cav ) in Figure a, and the band-edge regions in Figure b–d.…”
Section: Resultsmentioning
confidence: 99%
“…Although the main "red" fluorescence band of PS is known to originate from silicon nanocrystallites [19][20][21][22][23], the mechanism behind slower relaxation at longer detection wavelength in this band is still debatable. The wavelength dependent relaxation rate could be attributed to the size distribution of nanocrystallites, because fluorescence wavelength and probably its lifetime increase with the nanocrystallite size [25].…”
Section: Ps/r6gmentioning
confidence: 99%
“…Red fluorescence band usually attributed to nanometer sized Si nanocrystallites [19][20][21][22][23] is also inhomogeneous: fluorescence at different wavelengths decays with different rates and is attributed to nanocrystallites of different dimensions. Such behavior is also ambiguous -increasing relaxation times with longer detection wavelength could also be explained as a result of energy migration between nanocrystallites [14].…”
mentioning
confidence: 99%